The Application of Lego Play Therapy For Children at Risk of Developmental Disorders Due to Gadget Addiction - Tsalis, Shabrina; Firmansyah, Andan; Utami Asmarani, Sri (LPPM STIKes Muhammadiyah Ciamis, 2025)
Purpose: The purpose of this study is to examine the effectiveness of Lego play therapy in reducing gadget addiction among school-aged children who are at risk of developmental disorders. Methods: This study employed a qualitative design using a case study approach with a pediatric nursing care perspective. The subject was a 9-year-old girl experiencing gadget addiction. Lego play therapy was implemented over three consecutive days as an intervention to divert attention from gadget use while stimulating cognitive, creative, and social abilities. Results: The results demonstrated a reduction in the intensity of gadget use following the intervention. In addition, improvements were observed in the child’s cognitive function and social responsiveness, indicating positive behavioral changes after Lego play therapy. Conclusions: This case study concludes that Lego play therapy is effective in reducing gadget addiction in school-aged children. Beyond functioning as an attractive alternative to gadget use, Lego play therapy also supports cognitive and social development. Therefore, it can be considered a viable non-pharmacological intervention in pediatric nursing care to address challenges arising from excessive gadget use in the digital era.